The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/16878140211001194
|View full text |Cite
|
Sign up to set email alerts
|

Effects of boundary conditions on stress distribution of hydraulic support: A simulation and experimental study

Abstract: This paper analyzed the effects of boundary conditions on the stress distribution of hydraulic support with the static finite element (FE) model. Five loading conditions are considered in this study, including: 1) canopy torsional loading, 2) canopy eccentric loading, 3) base torsional loading, 4) base diagonal loading, and 5) base symmetrical loading. In order to verify the simulation results obtained from the FE model, the corresponding experiments have also been performed. Based on the comparison between si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…This testing process is well reproduced in the numerical simulation [18]. Lin et al [19] conducted a static simulation and experiment on a hydraulic support, by changing the contact mode between the pin and shaft hole, the effects of the boundary conditions on the stress distribution are discussed. He concluded that the bonded contact mode is the best way to simulate the experiment results.…”
Section: Introductionmentioning
confidence: 74%
“…This testing process is well reproduced in the numerical simulation [18]. Lin et al [19] conducted a static simulation and experiment on a hydraulic support, by changing the contact mode between the pin and shaft hole, the effects of the boundary conditions on the stress distribution are discussed. He concluded that the bonded contact mode is the best way to simulate the experiment results.…”
Section: Introductionmentioning
confidence: 74%
“…Meanwhile the mining height of the working face is also getting higher. These all cause the support to bear a large number of dynamic loads and reducing its reliability [8,12,22,27].…”
Section: Eksploatacja I Niezawodnosc -Maintenance and Reliabilitymentioning
confidence: 99%
“…When the basic roof breaks or gangue falls, the canopy will be affected by the impact load, resulting in the canopy being overloaded or unevenly loaded. In this case, the pin shaft at the canopy hinge often deforms, wears, and even breaks to varying degrees [5][6][7], which has a serious impact on the stable support of hydraulic support and underground safety operation.…”
Section: Introductionmentioning
confidence: 99%